2017
DOI: 10.1161/jaha.117.006887
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification (CAC) and Post‐Trial Cardiovascular Events and Mortality Within the Women's Health Initiative (WHI) Estrogen‐Alone Trial

Abstract: BackgroundAmong women aged 50 to 59 years at baseline in the Women's Health Initiative (WHI) Estrogen‐Alone (E‐Alone) trial, randomization to conjugated equine estrogen‐alone versus placebo was associated with lower risk of myocardial infarction and mortality, and, in an ancillary study, the WHI‐CACS (WHI Coronary Artery Calcification Study) with lower CAC, measured by cardiac computed tomography ≈8.7 years after baseline randomization. We hypothesized that higher CAC would be related to post‐trial coronary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…18 Similarly, breast cancer, cardiovascular disease, Alzheimer disease, and other WHI outcomes differed by CEE vs CEE þ MPA, with more favorable outcomes with CEE alone. 45 Consistent with other studies in the WHI and the claims database, the present study demonstrated the protective effect of CEE alone (oral CEE, 0.625 mg/day) in hysterectomized women, but not CEE þ MPA in women with a uterus. Whether the benefits of CEE alone generalize to women with a uterus is therefore unknown.…”
supporting
confidence: 92%
“…18 Similarly, breast cancer, cardiovascular disease, Alzheimer disease, and other WHI outcomes differed by CEE vs CEE þ MPA, with more favorable outcomes with CEE alone. 45 Consistent with other studies in the WHI and the claims database, the present study demonstrated the protective effect of CEE alone (oral CEE, 0.625 mg/day) in hysterectomized women, but not CEE þ MPA in women with a uterus. Whether the benefits of CEE alone generalize to women with a uterus is therefore unknown.…”
supporting
confidence: 92%
“…Recent evidence indicates that presence of any CAC, including those with low scores as we include here, is linked to coronary heart disease events and death. 31,32 Indeed, some have called for the inclusion of CAC screening to stratify women and men for treatment. 33 Our results raise important questions about how pregnancy history may help inform CVD screening and treatment guidelines for women.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we reported that estrogen can resist oxidative stress, protect endothelial function, and delay cellular aging 10. Several studies have also suggested the cardioprotective effects of estrogen, and its potential for the treatment of coronary heart disease 11,12. However, the long-term use of estrogen might pose serious health risks, including increasing the risk of cancer or thromboembolic disease,13,14 thereby limiting its clinical application.…”
Section: Introductionmentioning
confidence: 99%